1979
DOI: 10.1136/hrt.41.4.468
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cathodal, anodal, and bipolar strength-interval curves with temporary and permanent pacing electrodes.

Abstract: suMMARY Acute animal experiments indicate that ventricular vulnerability to fibrillation or multiple premature contractions is greater during bipolar or anodal stimulation than with unipolar cathodal (with electrodes of equal cathodal and anodal surface area) because the anodal and bipolar absolute refractory periods are shorter, enabling easier excitation in the vulnerable period. To compare the relative safety of stimulation with various commercial electrodes, strength-interval curves were determined in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…Weak electroporation also produces a slight increase of the relative refractory period, (from 20 to 27 ms). The break portion of the anodal S-I curves exhibits a typical dip followed by a dome and a subsequent sudden fall sharing the same features of the S-I curves observed experimentally in [146,324,480] and computed in [255,256,428]; we refer to [428] for an explanation of these features.…”
Section: Cathodal and Anodal Strength-interval S-i Curvessupporting
confidence: 71%
“…Weak electroporation also produces a slight increase of the relative refractory period, (from 20 to 27 ms). The break portion of the anodal S-I curves exhibits a typical dip followed by a dome and a subsequent sudden fall sharing the same features of the S-I curves observed experimentally in [146,324,480] and computed in [255,256,428]; we refer to [428] for an explanation of these features.…”
Section: Cathodal and Anodal Strength-interval S-i Curvessupporting
confidence: 71%
“…2) and increase in pacing thresholds (Table 1) as a result of tissue damage by pacing with strong current. The cathodal and anodal threshold values (Table 1) for the normal tissue are similar to those obtained by others (7,29). Tissue damage increases both thresholds three-to fourfold.…”
Section: Discussionsupporting
confidence: 74%
“…In the S-I curve, this interval appears as a "dip," and in the family of strength-duration curves, the period of increased excitability is manifested as displacement of the curves under stimulation during the relative refractory period (RRP) (25,36). Investigations of unipolar cathodal and anodal stimulation of the heart with short pulses revealed that periods of superexcitability are characteristic of positive (anodal) stimulation, whereas the S-I curve for negative (cathodal) stimulation is close to a hyperbolic shape (13,32).…”
mentioning
confidence: 98%